A case of skin damage due to overdose methotrexate poisoning - Zhe ZHUANG; Fanghua LIU; Wencong XU; Ruitao ZOU; Jiao ZHANG; Bihui YU; Hongfang LIU; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
We report a case of skin damage due to overdose methotrexate poisoning. A 74-year-old woman presented with erythema and desquamation of trunk and limbs accompanied with pain for 8 days. Before admission, MTX 5 mg/d was taken orally for 10 days, and the accumulative dose was 50 mg. On the third day of taking the medicine, erythema and desquamation appeared all over the body. Dermatology examination revealed that oral mucosal erosion and skin of trunk and limbs with erythema diffuse distributed, and erosion oozing on the surface of skin desquamated and some areas. Laboratory examinations revealed that the decreased number of leukocyte and platelets and elevated transaminase. The case was diagnosed with methotrexate poisoning. The patient was treated with Leucovorin, methylprednisolone, hydration, alkalized urine, recombinant human granulocyte stimulating factor, recombinant human thrombopoietin, topical medicine, and other symptomatic and supportive treatments. After 2-week treatments, the patient recovered.